Accuracy Analysis of GPS Positioning Near the Forest Environment - Pirti, Atinc (ZAGREB UNIV, FAC FORESTRY, 2008)
GPS has become an essential tool for georeferencing. In some cases, GPS is used for unfavorable conditions although it was developed for open field studies. This paper analyzes the achievable accuracy and performance of GPS near the forest. Three surveying marks have been established with the distance seperation five meter in length. Two GPS campaigns were conducted for the selected marks in the forest. The same campaign was repeated once again after the forest was cut off. The experiments demonstrate the degradation of the GPS accuracy due to the forest, As a result, the largest horizontal accuracy errors were found to be in the forest. Horizontal accuracy errors were the smallest in the area without obstacles. Large vertical accuracy errors were produced in the forest; however vertical accuracy errors were also relatively small after the forest was cut off. The standard deviations improved by about 50-70% for both baselines and height differences when the forest was cut off. In conclusion, tree canopies greatly affected both horizontal and vertical accuracy.
Keywords: GPS; forest; accuracy; terrestrial measurements; CANOPY; Forestry